2022
DOI: 10.1039/d2gc01966c
|View full text |Cite
|
Sign up to set email alerts
|

Redox-neutral ketyl radical coupling/cyclization of carbonyls withN-aryl acrylamides through consecutive photoinduced electron transfer

Abstract: While the reductive ketyl couplings of carbonyls have been widely explored, we report in this work on a redox-neutral umpolung carbonyl coupling reaction through ketyl radical formation by consecutive photoinduced...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
33
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 52 publications
(34 citation statements)
references
References 64 publications
(26 reference statements)
0
33
0
1
Order By: Relevance
“…Radical reactions, as a powerful tool in modern synthesis, have been rapidly developed in recent years, especially in combination with transition metal catalysis 8 and photocatalysis, 9 which enable radical-type couplings efficiently under mild radical excitation conditions. 8–10 2-Alkenyl benzaldehydes have been shown to be an excellent class of radical acceptors due to their unique structures in which unsaturated carbon–carbon double bonds and aldehyde groups coexist. They can be used to synthesize the valuable chroman-4-ols 11 and chroman-4-ones 12,13 through free radical intramolecular cyclization.…”
Section: Introductionmentioning
confidence: 99%
“…Radical reactions, as a powerful tool in modern synthesis, have been rapidly developed in recent years, especially in combination with transition metal catalysis 8 and photocatalysis, 9 which enable radical-type couplings efficiently under mild radical excitation conditions. 8–10 2-Alkenyl benzaldehydes have been shown to be an excellent class of radical acceptors due to their unique structures in which unsaturated carbon–carbon double bonds and aldehyde groups coexist. They can be used to synthesize the valuable chroman-4-ols 11 and chroman-4-ones 12,13 through free radical intramolecular cyclization.…”
Section: Introductionmentioning
confidence: 99%
“…Given that the hydrogen-borrowing strategy has been well established in transition-metal-catalyzed dehydrogenative aromatization, we speculated that this strategy could merge photoredox catalysis to enable mild oxidative dehydrogenation and hydrogen-borrowing reduction in one process. Within our ongoing program on synthetic sustainable chemistry, we report herein a mild visible-light-induced hydrogen-borrowing reduction/dehydrogenative aromatization strategy for the intramolecular dehydrative cyclization of 2-substituted nitroarenes bearing tetrahydropyrimidine and cyclohexene. Hence, structurally valuable pyrimidoindazoles and carbazoles have been readily accessed in an atom-economic manner (Figure c).…”
mentioning
confidence: 99%
“…35 Very recently, Huang's group employed the ConPET system of 4CzIPN to achieve the additive-free reduction of benzaldehyde (E 1/2 red = −1.92 V vs SCE). 36 Inspired by the above elegant works, we envisioned that 4-cyanopyridine could be reduced by the generated 4CzIPN •− * in the ConPET process (Scheme 1). On the other hand, the photocatalytic decarboxylation process enabled by the photocatalytic oxidation of 4CzIPN* should be feasible.…”
mentioning
confidence: 99%
“…As shown in Figure S3, the cyclic voltammogram experiment further confirmed that the excited state of 4CzIPN (E 1/2 ox = +1.35 V vs SCE) 43 could be reductively quenched by the 2a Cs salt (E 1/2 ox = +0.9 V vs SCE). Consistent with the result reported by Wu's group 35 and Huang's group, 36 we observed that the emission of the solution of 4CzIPN and 2a Cs salt underwent an obvious hypsochromic shift (λ max from 546 to 477 nm, Scheme 5c) after irradiation of a purple LED, suggesting the formation of a new species with fluorescence emission property.…”
mentioning
confidence: 99%
See 1 more Smart Citation